Sampling impacts the assessment of tooth growth and replacement rates in archosaurs: implications for paleontological studies - Kosch,Jens C.D.; Zanno,Lindsay E. (PeerJ, 2020)
Dietary habits in extinct species cannot be directly observed; thus, in the absence of extraordinary evidence, they must be reconstructed with a combination of morphological proxies. Such proxies often include information on dental organization and function such as tooth formation time and tooth replacement rate. In extinct organisms, tooth formation times and tooth replacement rate are calculated, in part via extrapolation of the space between incremental lines in dental tissues representing daily growth (von Ebner Line Increment Width; VEIW). However, to date, little work has been conducted testing assumptions about the primary data underpinning these calculations, specifically, the potential impact of differential sampling and data extrapolation protocols. To address this, we tested a variety of intradental, intramandibular, and ontogentic sampling effects on calculations of mean VEIW, tooth formation times, and replacement rates using histological sections and CT reconstructions of a growth series of three specimens of the extant archosaurian Alligator mississippiensis. We find transect position within the tooth and transect orientation with respect to von Ebner lines to have the greatest impact on calculations of mean VEIW—a maximum number of VEIW measurements should be made as near to the central axis (CA) as possible. Measuring in regions away from the central axis can reduce mean VEIW by up to 36%, causing inflated calculations of tooth formation time. We find little demonstrable impact to calculations of mean VEIW from the practice of subsampling along a transect, or from using mean VEIW derived from one portion of the dentition to extrapolate for other regions of the dentition. Subsampling along transects contributes only minor variations in mean VEIW (<12%) that are dwarfed by the standard deviation (SD). Moreover, variation in VEIW with distance from the pulp cavity likely reflects idiosyncratic patterns related to life history, which are difficult to control for; however, we recommend increasing the number of VEIW measured to minimize this effect. Our data reveal only a weak correlation between mean VEIW and body length, suggesting minimal ontogenetic impacts. Finally, we provide a relative SD of mean VEIW for Alligator of 29.94%, which can be used by researchers to create data-driven error bars for tooth formation times and replacement rates in fossil taxa with small sample sizes. We caution that small differences in mean VEIW calculations resulting from non-standardized sampling protocols, especially in a comparative context, will produce inflated error in tooth formation time estimations that intensify with crown height. The same holds true for applications of our relative SD to calculations of tooth formation time in extinct taxa, which produce highly variable maximum and minimum estimates in large-toothed taxa (e.g., 718–1,331 days in Tyrannosaurus).
Keywords: Tooth formation; Tooth replacement; Archosauria; Sampling effects; Alligator; von Ebner lines; Error bars